2012
DOI: 10.1258/ar.2012.110017
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium-chitosan nanoparticles as a novel contrast agent for potential use in clinical bowel-targeted MRI: a feasibility study in healthy rats

Abstract: Gd@chitosan nanoparticles with high Gd-DTPA content were successfully prepared for use as a novel MRI contrast agent. All results indicated that rectally administered Gd@chitosan nanoparticles have the potential for MRI diagnosis of colon mucosal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…Molecular MR imaging was facilitated in all 8 studies except for one, in which MRI was combined with single-photon emission computed tomography (SPECT/CT) [9]. Positive contrast agent was employed in 3 studies which showed abnormal strengthening in inflammation or colitis-associated dysplasia [10,13,14]. Another 2 groups used magnetic nanoparticles (MNPs) that showed signal intensity decreases in inflammatory lesions [9,11].…”
Section: Subjectsmentioning
confidence: 99%
See 3 more Smart Citations
“…Molecular MR imaging was facilitated in all 8 studies except for one, in which MRI was combined with single-photon emission computed tomography (SPECT/CT) [9]. Positive contrast agent was employed in 3 studies which showed abnormal strengthening in inflammation or colitis-associated dysplasia [10,13,14]. Another 2 groups used magnetic nanoparticles (MNPs) that showed signal intensity decreases in inflammatory lesions [9,11].…”
Section: Subjectsmentioning
confidence: 99%
“…e majority of studies used mice aged 5 to 8 weeks except for one study which used adult mice. Two studies adopted Lewis rats aged 8 to 12 weeks with an average weight of 220 to 270 g and Sprague Dawley rats with a 190 to 210 g body weight [10,14]. e final study used a healthy rabbit at 2.7 kg in mass [15].…”
Section: Experimental Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…CT and MRI are the most common imaging modalities, and there are many potential future directions for the diagnosis of GI diseases, such as precisely targeting diseased sites, designing smart contrast agents, and multimodal imaging methods. For example, gadolinium acid can be loaded in chitosan nanoparticles and used to target detection of colon mucosa diseases by MRI . Electrospun core–shell fibers have also been designed for sustained release of contrast agents and for the detection of colonic abnormities .…”
Section: Perspectivesmentioning
confidence: 99%